Leveraging financial literacy into sustainable business performance: a mediated-moderated model - Ratnawati, Kusuma; Koval, Viktor; Arsawan, I Wayan Edi; Kazancoglu, Yigit; Lomachynska, Iryna; Skyba, Hanna (Business, Management and Economics Engineering, 2024)
Purpose – The current study evaluates the linkage between financial literacy and the sustainable business performance model with access to finance and fintech adoption. Further, the moderating role of top management support in the linkage between financial literacy toward access to finance and fintech adoption was verified.Research methodology – This research was conducted in the SME sector in Indonesia. The sample frame were 261 SMEs and 783 respondents from three levels of management. Data was collected in the October-December 2023 period. Data were obtained utilizing Likert-scaled questionnaires and analyzed using SmartPLS.Findings – The results demonstrate that financial literacy is an instrumental driver of access to finance and fintech adoption that promotes sustainability performance. Subsequently, the study highlights the critical role of access to finance and fintech adoption as the mediator and top management support as moderator.Research limitations – The study is solely performed on the SME sector in one country; thus, the findings’ generalization is lacking.Practical implications – SME managers need to upgrade their financial literacy because financially knowledgeable managers are keenly informed of the costs, benefits, and risks related to funding schemes to encourage sustainable performance.Originality/Value – Empirical research that explores the implication of financial literacy on access to finance and fintech adoption in promoting sustainability performance is lacking, reported solely on manufacturing companies and banks. Meanwhile, the SME sector, especially in developing countries, is understudied. Consequently, the initial study leads the examination of financial literacy’s role in enhancing access to finance and fintech adoption to foster the sustainability performance of SMEs.